Evaluating Petronas strategies in international business with China / Hashim Majid and Herman Putra Mohd Nazri - Majid, Hashim; Mohd Nazri, Herman Putra (Faculty of Business and Management, 2005)
During the last half of the twentieth century, many barriers to international trade fell and a wave of firms began pursuing global strategies to gain a competitive advantage. However, some industries benefit more from globalisation than do others, and some nations have a comparative advantage over other nations in certain industries. To create a successful global strategy, managers first must understand the nature of global industries and the dynamics of global competition. There are many hurdles of doing business in China. One of the biggest hurdles is coming to terms with the real China, a land of great geographical, social, political, and industrial diversity. As a starting point, it's essential to cut through the thicket of misunderstandings and misinformation about doing business there. China's overall energy consumption ranks second in the world. Their energy demand will continue to rise over the next five years. China's growing demand for energy has caused this traditionally off-limits sector to gradually open up to increasingly larger scale foreign participation. Good opportunities exist in both upstream and downstream engineering, project supervision, license, and equipment, technology, consulting, marketing and supply sectors. PETRONAS has business interests in 35 countries. A Fortune 500 company, it first entered China in 1991 in the oil and gas exploration sector. Since then, the company has expanded into the downstream sector. In the early stage, PETRONAS took strategic approach by Joint Venture in China. We would like to note here that PETRONAS early Joint Venture in China did note face any marketing issue. However, problems appeared when they ventured into Wholly Owned subsidiary. From the Group's findings and analysis, we conclude that PETRONAS marketing department should be more aggressive. Also, in order to be more competitive and earn above average returns, they should form wholly owned subsidiary and expand horizontally. The future is bright with China's vast affluent market. It is hoped that this project paper would contribute positively to PETRONAS in general and PMCCL specifically in their endeavour in China.